Implementation of Qur’anic Character Strengthening through Mabit and Tadabbur Alam at The Educational Institution Rumah Tahfidz - Melkya Khailana Tantri; Kutsiyyah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Strengthening Qur'anic character is a key focus in Islamic education to address today's moral challenges. This study aims to examine the implementation of Qur'anic character strengthening through the integration of mabit and tadabbur alam activities at Rumah Tahfidz Ar-Rahman Sampang, as well as to identify the supporting and inhibiting factors. Unlike previous studies, this research emphasizes the integration of these two programs as an experiential character-building model. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that the program successfully instills Qur'anic values, including taqwa, istiqamah, tawakal, discipline, perseverance, tawadhu', honesty, mutual respect, filial piety, environmental care, and gratitude. Its implementation is supported by the role of asatidz, students' awareness, and a conducive environment, while obstacles include differences in students' character, limited parental support, and constraints in time and facilities. This study contributes a new experience-based model for strengthening Qur'anic character in Rumah Tahfidz.